PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD OLEH GURU PAK DALAM PENINGKATAN HASIL BELAJAR SISWA - Yesika Mida Gloria Sibatuara; Lustani Samosir; Ronny Simatupang; Lasmaria Lumban Tobing; Ordekoria Saragih (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The purpose of this study was to determine the effect of the implementation of the Student Achievement Division (STAD) type cooperative learning model by Christian Religious Education and Character Education teachers on the learning outcomes of class XI students of SMA Negeri 1 Doloksanggul in the 2025/2026 academic year. Research hypothesis: There is an effect of the implementation of the STAD type cooperative learning model by Christian Religious Education and Character Education teachers on the learning outcomes of students in the 80 grade category of class XI of SMA Negeri 1 Doloksanggul in the 2025/2026 academic year. The population of all Protestant Christian students of class XI of SMA Negeri 1 Doloksanggul in the 2025/2026 academic year = 325 students consisting of 10 classes. The research sample was determined using a purposive sampling technique, namely class XI-5 = 30 students (experimental) and class XI-3 = 30 students (control). The research method used a quantitative method of the Quasy Experimental Design type with a Nonequivalent Control Group Design. The research instrument was a question for the Y variable of 28 items. N-Gain Score of experimental class = 0.4367 medium category, control class = 0.0687 low category. thitung = 6.216 > ttabel (? = 5%) = 1.671 and the average posttest score of experimental class students' learning outcomes = 83>80. It can be concluded that the research hypothesis is accepted, namely there is an influence of the application of the STAD type cooperative learning model by Christian Religious Education and Character Education teachers on the learning outcomes of class XI students of SMA Negeri 1 Doloksanggul in the 2025/2026 academic year.   Keywords: STAD model, student learning outcomes   Abstrak: Tujuan penelitian ini untuk mengetahui Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Student Achievement Division (STAD) Oleh Guru Pendidikan Agama Kristen dan Budi Pekerti Terhadap Hasil Belajar Siswa kelas XI SMA Negeri 1 Doloksanggul Tahun Pembelajaran 2025/2026. Hipotesis penelitian: Terdapat pengaruh penerapan model pembelajaran kooperatif tipe STAD oleh guru Pendidikan Agama Kristen dan Budi Pekerti terhadap hasil belajar siswa pada kategori nilai 80 kelas XI SMA Negeri 1 Doloksanggul tahun pembelajaran 2025/2026. Populasi seluruh siswa Kristen Protestan kelas XI SMA Negeri 1 Doloksanggul tahun pembelajaran 2025/2026= 325 siswa terdiri dari 10 kelas. Sampel penelitian ditetapkan menggunakan teknik purposive sampling yaitu kelas XI-5= 30 siswa (eksperimen) dan kelas XI-3= 30 siswa (kontrol). Metode penelitian menggunakan metode kuantitatif jenis Quasy Experimental Design dengan desain Nonequivalent Control Group Design. Instrumen penelitian ini adalah soal untuk variable Y sebanyak 28 item. N-Gain Skor kelas eksperimen= 0,4367 kategori sedang, kelas kontrol= 0,0687 kategori rendah. thitung= 6,216 > ttabel(?=5%)= 1,671 dan nilai posttest rata-rata hasil belajar siswa kelas eksperimen= 83>80 . Dapat disimpulkan hipotesis penelitian diterima yaitu terdapat pengaruh penerapan model pembelajaran kooperatif tipe STAD oleh guru Pendidikan Agama Kristen dan Budi Pekerti terhadap hasil belajar siswa kelas XI SMA Negeri 1 Doloksanggul tahun pembelajaran 2025/2026   Kata kunci: model STAD, hasil belajar siswa